PENGARUH KECERDASAN LOGIS MATEMATIS DAN EFIKASI DIRI TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Anita Amaelia Sari; Lambok Simamora; Rita Ningsih (CV Putra Publisher, 2022)
The purpose of this study was to determine the effect of mathematical logical intelligence and self-efficacy on mathematical problem solving abilities. This research method uses a survey method. The population in this study were 277 students. The sample used was 74 students. This research was conducted using a questionnaire and a test with a sample of 30 students. The sampling technique used is random sampling technique. Measurement and data collection of students' mathematical problem solving abilities using a written test instrument in the form of an essay totaling 6 valid questions and taking data on mathematical logical intelligence and self-efficacy using a questionnaire totaling 22 questions and 24 valid questions. The results showed that the significant test was obtained Fℎ???????????????????? = 139.969 while F???????????????????? = 3, 13 which stated that was rejected and 1 was accepted, which means that there is a significant influence between mathematical logical intelligence and self-efficacy on mathematical problem solving abilities.